Passivum divinum w Tanachu i Biblii Lutra - Termińska-Korzon, Kamilla; Tobiasz, Lesław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
Passivum divinum is a characteristic of utterances related in an overt, hidden, or presupposed way to divine activities formulated in the passive voice. Passivum divinum emphasizes Divine Agent’s action in utterances that use repetition of particularly sublime structure, and it characterizes divine performative utterances. Passivum is also used to share responsibility with another agent for a particular action of the Divine Initiator, expressing in this way “the idea of G-d’s secretiveness”. Passivum divinum also creates space for action in this “best of all worlds” of evil powers. Since passive grammatical formations in Biblical Hebrew, German, and Polish are differently semanticized, there is possibility of achieving full, either dynamic or formal, translatory equivalence.